2007
DOI: 10.1364/oe.15.000945
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observations of dual-polarization oscillations in laser-diode-pumped wide-aperture thin-slice Nd:GdVO_4 lasers

Abstract: Dual-polarization oscillations (DPO) on different transitions have been observed for the first time in a mirror-coated thin-slice Nd:GdVO(4) laser possessing a large fluorescence anisotropy with laser-diode (LD) pumping. Oscillation spectra, input-output characteristics, pump-dependent pattern formations and noise power spectra are studied experimentally. Simultaneous oscillations of orthogonally-polarized different (higher-order) transverse modes and the resultant violation of inherent antiphase dynamics in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Modes 1 and 1 are linearly π -polarized modes belonging to the 4 belonging to the 4 F 3/2 (2) → 4 I 11/2 (2) and 4 F 3/2 (1) → 4 I 11/2 (1) transitions at 1065.42 nm and 1063.04 nm, respectively. The polarization properties of those modes were also determined in our previous work [7]. In figure 2(a), the output of the σ -polarized emission typically decreased with rising pump power and stopped lasing in the end.…”
Section: Magnification Of Objective Lensmentioning
confidence: 68%
See 2 more Smart Citations
“…Modes 1 and 1 are linearly π -polarized modes belonging to the 4 belonging to the 4 F 3/2 (2) → 4 I 11/2 (2) and 4 F 3/2 (1) → 4 I 11/2 (1) transitions at 1065.42 nm and 1063.04 nm, respectively. The polarization properties of those modes were also determined in our previous work [7]. In figure 2(a), the output of the σ -polarized emission typically decreased with rising pump power and stopped lasing in the end.…”
Section: Magnification Of Objective Lensmentioning
confidence: 68%
“…Cai et al [5] investigated the dual polarization in a diode-pumped c-cut Nd:YVO 4 laser resulting from competition between overlapping transitions. Dual polarization oscillations have also been observed in laserdiode-pumped Nd:GdVO 4 lasers with a large fluorescence anisotropy [6,7]. The previous study [7] suggested that dual polarization oscillations depend on pump-beam focusing conditions, which affect the lasing properties due to the pump-radius-dependent thermal lens effect [8].…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Figures 4(a) shows the polarization-dependent power spectral intensity, I RO (), at the intrinsic relaxation oscillation frequency, f 1 , and the lower frequency relaxation noise peak, f 2 , in Figure 3(b), while Figure 4(b) shows the polarization-dependent power spectral intensity, I b (), at the beating frequencies, f b,1 and f b,2 , which are relevant to the BSW oscillations. Note that f 2 relaxation oscillations resulting from the inherent transverse cross-saturation of population inversions among modes [21] are strongly suppressed at the critical polarization directions,  c = 50.5 o and 131.5 o , as shown in Figure 4(c). Here, the critical angles are given by  c ≅ arctan(±1/r) when subsidiary peaks are much smaller compared with the dominant peaks, i.e., E 3 ≪ E 1 and E 4 ≪ E 2 , where r = (I 2 /I 1 ) 1/2 is the field amplitude ratio of DPO eigenmodes in Figure 1(b), where the field components of the orthogonally polarized eigenmodes along  c coincide and the effective modal gain for one mode coincides with that of the other mode [12].…”
Section: Measurement Of Polarization-dependent Power Spectra Of Bsw Omentioning
confidence: 86%
“…2(b), together with that for the total output. The f1-peak corresponds to the fundamental relaxation oscillation noise, while the f2-peak arises through transverse cross-saturation of population inversions of orthogonally polarized modes [16]. Note that the lower frequency peak at f2 is suppressed in the total output.…”
mentioning
confidence: 99%